2009
DOI: 10.1111/j.1365-2427.2009.02190.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bacteria and benthic invertebrates as indicators of ecological health in streams

Abstract: 1. We set out to evaluate the reliability of bacterial communities as an indicator of freshwater ecological health. 2. Samples of epilithic biofilm were taken over a 1-year period from four streams, each impacted by varying degrees of human modification. The bacteria within each sample were characterised using a whole community DNA fingerprinting technique (automated ribosomal intergenic spacer analysis). Spatial and temporal differences in community structure between samples were visualised using multi-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Site 1 is home to diverse and abundant benthic macroinvertebrates, while site 4 has a macrobenthic invertebrate fauna of very low diversity, consisting almost entirely of chironomid larvae (38). Biofilms at site 1 may therefore be subjected to very different grazing pressures than biofilms at site 4, which is likely to further affect the nutrient resources available in these streams.…”
Section: Vol 75 2009 Diversity Of Ciliates In Stream Biofilms 5267mentioning
confidence: 99%
“…Site 1 is home to diverse and abundant benthic macroinvertebrates, while site 4 has a macrobenthic invertebrate fauna of very low diversity, consisting almost entirely of chironomid larvae (38). Biofilms at site 1 may therefore be subjected to very different grazing pressures than biofilms at site 4, which is likely to further affect the nutrient resources available in these streams.…”
Section: Vol 75 2009 Diversity Of Ciliates In Stream Biofilms 5267mentioning
confidence: 99%
“…Nevertheless, the analysis of microbial communities may provide a useful alternative measure of ecosystem health since (1) microorganisms are ubiquitous and require little sampling effort, (2) there is minimal site disturbance associated with collecting small volumes of sediment, biofilm or water for microbial community analysis, (3) the rapid life cycle of microorganisms means they may be rapid indicators of environmental change and (4) numerous methods are now available with which to characterise the genetic diversity of aquatic microbial communities using rapid community DNA fingerprinting techniques such as denaturing gradient gel electrophoresis (DGGE; Lyautey et al 2003), terminal restriction fragment length polymorphism (T-RFLP; Dopheide et al 2009) and automated ribosomal intergenic spacer analysis (ARISA; Jones et al 2007). For example, Lear et al (2009a) recently used ARISA to characterise bacterial communities within stream biofilms and identified that these communities could provide a more sensitive indicator of ecological health than macroinvertebrates within highly impacted streams. Adopting a similar approach, Stein et al (2010) analysed the fauna and bacteria within groundwater aquifers revealing that both communities responded to the environmental impacts occurring on the surface of the land.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial community composition within every sample was analysed using automated ribosomal intergenic spacer analysis (or ARISA) following the method of (Lear et al, 2009) with the primers LDBact (5 0 -CCGGGTTTCCCCATTCGG-3 0 ) and SDBact (5 0 -TG CGGCTGGATCCCCTCCTTC-3 0 ) (Ranjard et al, 2001). The protocol of Ramette (2009) was used to identify 'true peaks' from ARISA electropherograms (that is, removing background noise generated during automated analysis) and bin fragments of similar size (using a selection window of 2 bp with a shift size of 0.1 bp).…”
Section: Bacterial Biogeography In Alpine Ponds G Lear Et Almentioning
confidence: 99%